Quantifying Soundscapes in the Ross Sea, Antarctica Using Long-Term Autonomous Hydroacoustic Monitoring Systems - Yun, Sukyoung; Lee, Won Sang; Dziak, Robert P.; Roche, Lauren; Matsumoto, Haruyoshi; Lau, Tai-Kwan; Sremba, Angela; Mellinger, David K.; Haxel, Joseph H.; Kang, Seung-Goo; Hong, Jong Kuk; Park, Yongcheol (Frontiers in Marine Science, 2021)
Deployment of long-term, continuously recording passive-acoustic sensors in the ocean can provide insights into sound sources related to ocean dynamics, air–sea interactions, and biologic and human activities, all which contribute to shaping ocean soundscapes. In the polar regions, the changing ocean climate likely contributes to seasonal and long-term variation in cryogenic sounds, adding to the complexity of these soundscapes. The Korea Polar Research Institute and the U.S. National Oceanic and Atmospheric Administration have jointly operated two arrays of autonomous underwater hydrophones in the Southern Ocean, one in the Terra Nova Bay Polynya (TNBP) during December 2015–January 2019 and the other in the Balleny Islands (BI) region during January 2015–March 2016, to monitor changes in ocean soundscapes. In the BI region, we found distinct seasonal variations in the cryogenic signals that were attributed to collisions and thermal/mechanical fracturing of the surface sea ice. This is consistent with sea-ice patterns due to annual freeze–thaw cycles, which are not clearly observed in TNBP, where frequent blowing out of sea ice by katabatic winds and icequakes from nearby ice shelves generate strong noise even in austral winters. Another advantage of passive acoustic recordings is that they provide opportunities to measure biodiversity from classifying spectral characteristics of marine mammals: we identified 1. Leopard seals (Hydrurga leptonyx; 200–400 Hz), most abundant in the BI region and TNBP in December; 2. Antarctic blue whales (Balaenoptera musculus; distinctive vocalization at 18 and 27 Hz), strong signals in austral winter and fall in the BI region and TNBP; 3. Fin whales (B. physalus; fundamental frequency in the 15–28 Hz and overtones at 80 and 90 Hz), maximum presence in the BI region during the austral summer and spring months; 4. Antarctic minke whales (B. bonaerensis; 100–200 Hz), strongest signals from June to August in the BI region; 5. Humpback whales in TNBP; 6. Unidentified whales (long-duration downsweeping from 75 to 62 Hz), detected in TNBP. Long-term soundscape monitoring can help understand the spatiotemporal changes in the Southern Ocean and cryosphere and provide a means of assessing the status and trends of biodiversity in the Ross Sea Region Marine Protected Area.